Wealth and want - Lebergott, Stanley (Princeton University Press, 1975)
There exist eight reliable ways to increase poverty and the United States is now pursuing seven of them, according to Lebergott. His provocative examination of income and wealth in this country reveals the impossibility of ending poverty permanently without changing American capitalism beyond recognition. Originally published in 1976. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.